Design, synthesis, biological evaluation, and computational insights of 2-(Aryl)benzo[d]imidazo[2,1-b]thiazole-7-sulfonamide derivatives as potent antitubercular and antibacterial agents - Hemant S. Deshmukh; Vishnu A. Adole; Suraj N. Mali; Bapu S. Jagdale (BMC Chemistry)
Abstract A series of 2-(aryl)benzo[d]imidazo[2,1-b]thiazole-7-sulfonamide derivatives were synthesized and evaluated for their antitubercular and antibacterial activities, molecular docking, and DFT studies. The compounds were synthesized through a multi-step reactions, with yields varying based on the electronic and steric effects of the substituents. Among the derivatives, 5b, 5d, and 5h exhibited potent antitubercular activity against Mycobacterium tuberculosis (H37Rv strain) with minimum inhibitory concentrations (MICs) of 1.6 µg/mL, comparable to some standard drugs like isoniazid. Antibacterial testing revealed that 2-(2,4-dichlorophenyl)benzo[d]imidazo[2,1-b]thiazole-7-sulfonamide displayed significant activity against Gram-positive bacteria, with MICs as low as 6.25 µg/mL for Staphylococcus aureus and Bacillus subtilis. The molecular docking and DFT analyses provided insights into the binding interactions and electronic structures of these compounds, with halogen substitutions enhancing biological activity due to increased electron-withdrawing effects. MESP studies showed a distinct electron density distribution, supporting the observed bioactivity. For antitubercular activity, compounds 5b, 5d, and 5h demonstrated potent binding affinities (−6.2 to −5.9 kcal/mol) against the DprE1 enzyme. Compound 5f showed remarkable antibacterial efficacy, with a docking score of −7.9 kcal/mol against 2,2-dialkylglycine decarboxylase The DFT analysis revealed that 5a, with a methoxy substituent, had the highest reactivity (ΔE = 3.86 eV), while halogenated derivatives, such as 5f, exhibited increased chemical stability (ΔE = 4.24 eV). ADME studies showed that 5f having favorable lipophilicity and enzyme inhibition. These findings suggested that these derivatives could serve as potential candidates for further drug development against bacterial and mycobacterial infections. Graphical Abstract